2006
DOI: 10.1007/s00421-006-0321-7
|View full text |Cite
|
Sign up to set email alerts
|

Constant versus variable-intensity during cycling: effects on subsequent running performance

Abstract: The aim of this study was to investigate the metabolic responses to variable versus constantintensity (CI) during 20-km cycling on subsequent 5-km running performance. Ten triathletes, not only completed one incremental cycling test to determine maximal oxygen uptake and maximal aerobic power (MAP), but also three various cycle-run (C-R) combinations conducted in outdoor conditions. During the C-R sessions, subjects performed first a 20-km cycletime trial with a freely chosen intensity (FCI, ~80% MAP) followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
2
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 32 publications
3
26
2
2
Order By: Relevance
“…First of all, we used a cycling section at the intensity corresponding to the Th vent that lasted 30 min as this has been shown to produce a modified cardiorespiratory response from that observed during an isolated control run (10-11, 16-18, 20). Secondly, we chose a 3-km time-trial to assess running performance because said distance has been both implemented before in specific-T2 tests (3)(4) and demonstrated to be sufficient to determine the possible effects of neuromuscular fatigue on performance (30).…”
Section: Limitationsmentioning
confidence: 99%
“…First of all, we used a cycling section at the intensity corresponding to the Th vent that lasted 30 min as this has been shown to produce a modified cardiorespiratory response from that observed during an isolated control run (10-11, 16-18, 20). Secondly, we chose a 3-km time-trial to assess running performance because said distance has been both implemented before in specific-T2 tests (3)(4) and demonstrated to be sufficient to determine the possible effects of neuromuscular fatigue on performance (30).…”
Section: Limitationsmentioning
confidence: 99%
“…To simplify the examination of pacing strategy on performance, the present and other studies compared effects of highly regular, alternately high and low power profiles with those from equivalent, but constant, mean external power outputs. A similar approach has occurred in investigations of physiological response (Lepers, Theurel, Hausswirth, & Bernard, 2008; and performance consequences of variable-power strategies (Bernard et al, 2007;Suriano, Vercruyssen, Bishop, & Brisswalter, 2007) and results have been equivocal. However, the highly regular periods and amplitudes of variation presented in the present and other studies are unlikely to represent the periods and amplitudes of variation that occur during self-paced trials (Jobson, Passfield, Atkinson, Barton, & Scarf, 2009).…”
mentioning
confidence: 95%
“…During the last decade, triathlon, involving successive swimming, cycling, and running sessions, has become one the most popular multidisciplinary event. Studies focusing on factors affecting performance during a triathlon have clearly identified differences with single performance, indicating that the effect of previous locomotion mode on subsequent exercise was the main factor explaining changes in performance (Bentley, Millet, Vleck, & McNaughton, 2002;Bernard et al, 2007;Hausswirth & Lehénaff, 2001). Therefore the adaptation of triathletes must be considered as unique and relatively specific to the constraints activity (race profile, swim-cycle and cycle-run transitions, intensity, and exercise duration).…”
mentioning
confidence: 99%